Suppression of Natural Killer cell NKG2D and CD226 anti-tumour cascades by platelet cloaked cancer cells: Implications for the metastatic cascade - Gardiner, Clair; O'Toole, Sharon; Sheils, Orla; O'Leary, John (My University, 2019)
Tumour cell immune evasion is a principal hallmark of successful metastasis. Tumour cells in the vasculature adopt a platelet cloak that efficiently suppresses the innate immune system by directly inhibiting Natural Killer (NK) cells, which normally function to neutralise spreading cancers. Here we describe two novel mechanisms of tumour cell evasion of NK cell anti-tumour functions. The first, an ‘immune decoy’ mechanism in which platelets induce the release of soluble NKG2D ligands from the tumour cell to mask detection and actively suppress NK cell degranulation and inflammatory cytokine (IFNγ) production, concomitantly. This represents a double-hit to immune clearance of malignant cells during metastasis. The second mechanism, a platelet-derived TGFβ-mediated suppression of the CD226/CD96-CD112/CD155 axis, is a novel pathway with poorly understood anti-cancer functions. We have demonstrated that platelets robustly suppress surface expression of CD226 and CD96 on the NK cell surface and their associated ligands on the tumour cell to further enhance NK cell suppression. These highly evolved mechanisms promote successful tumour immune evasion during metastasis and provide a unique opportunity for studying the complexity of cellular interactions in the metastatic cascade and thus novel targets for cancer immunotherapy.
PUBLISHED
cited By 2
Keywords: Tumour cell immune evasion; Natural killer cells; Platelet activation; Platelets; Melanoma cells; Melanomas; Flow cytometry; Immune evasion; Enzyme-linked immunoassays; Tumour cell immune evasion